(untitled) (Al-Malwiya Journal of Sport and Movement Sciences, 2026)
In-season resistance training in football must balance strength development with recovery demands of match play and technical training. This study examined the effects of a 16-week periodised resistance training programme on maximal strength (1RM back squat), lower limb power (countermovement jump height, CMJ), and 30-metre sprint performance in elite Iraqi male football players. Thirty-eight players from two Iraqi Premier League clubs were assigned to either a periodised resistance training group (RTG, n = 19) or a technical-only control group (CG, n = 19). The RTG performed two weekly resistance sessions using a block periodisation model. Post-intervention, the RTG demonstrated significantly greater improvements in 1RM squat (Delta = +18.4 kg; p < 0.001; d = 2.47), CMJ height (Delta = +4.6 cm; p < 0.001; d = 2.11), and 30-metre sprint time (Delta = -0.18 s; p < 0.001; d = 1.98) compared to the CG. No significant between-group differences in injury rates or training load markers were observed. These results support the integration of block-periodised resistance training into the in-season programme of elite Iraqi football players.